Condition of the humoral link of immune system at patients with endometrial cancer - A. V. Efremov; N. A. Matveevskij; A. N. Trunov; I. D. Safronov (ABV-press, 2014)
Examine changes in the parameters reflecting the activation of humoral immune system, the severity of the destructive processesand autoimmune reactions in patients with endometrial cancer . The findings suggest that the significance of activation of autoimmune reac tions and destructive processes in pathogenetic mechanisms of development of malignant tumors of the corpus uteri.